Hubungan antara Religious Fundamentalism dan Sikap terhadap Kebijakan Publik yang Terkait dengan Pembaruan Pemikiran Islam - Vinaya (Fakultas Psikologi Universitas Pancasila, 2011)
This study examines the correlation between religious fundamentalism and attitude towards public policies related to progressive Islamic thought. The respondents are Moslem and have at least graduated from senior high school. Religious fundamentalism scale (Altemeyer & Hunsberger, 2004) and attitude towards public policies related to progressive Islamic thought scale are used on 453 respondents. The result shows that religious fundamentalism has a negative correlation with attitude towards public policies related to progressive Islamic thought. On the other hand, educational level has positive and significant correlation with attitude towards public policies related to progressive Islamic thought.